La piedra de la paciencia = (Sangue sabur) - Rahimi, Atiq (Nuevos tiempos (Madrid, Spain), 2012)
In Persian folklore, Syngue Sabour is the name of a magical black stone, a patience stone, which absorbs the plight of those who confide in it. It is believed that the day it explodes, after having received too much hardship and pain, will be the day of the Apocalypse. But here, the Syngue Sabour is not a stone but rather a man lying brain-dead with a bullet lodged in his neck. His wife is with him, sitting by his side. But she resents him for having sacrificed her to the war, for never being able to resist the call to arms, for wanting to be a hero, and in the end, after all was said and done, for being incapacitated in a small skirmish.